Using genomic structural equation modeling to examine the genetic architecture of PTSD and life satisfaction phenotypes - Shannon E. Cusack; Anna W. Wright; Peter B. Barr; Emily Notari; Kaitlin E. Bountress; Ananda B. Amstadter (European Journal of Psychotraumatology)
Objective: Posttraumatic stress disorder (PTSD) and life satisfaction phenotypes are inversely related on a phenotypic level. Given these established relations, researchers have begun to examine possible shared genetic contributions to these outcomes, though the existing genetic literature is sparse and examines these relations via univariate methods. We sought to examine the genetic architecture of PTSD and six life satisfaction and well-being phenotypes (i.e. subjective well-being, friend satisfaction, life satisfaction, family satisfaction, work satisfaction, and financial satisfaction) using a multivariate approach.Method: We used Genomic Structural Equation Modeling (gSEM) to analyze summary-level genetic data from large-scale GWAS of the European Ancestry.Results: Findings show that a two, correlated factors model fit the data best, in which PTSD and life satisfaction phenotypes load on separate but correlated factors.Conclusions: Findings suggest that, using multivariate methods, a latent factor capturing many different positive phenotypes is genetically related to PTSD. This finding confirms and extends prior phenotypic work demonstrating that PTSD and positive phenotypes are inversely related.